The Influence of Environmental, Social and Governance (ESG) on Debt Costs in Companies Energy Sectors Listed on the IDX - Nurul Nurul; Ari Agung Nugroho; Darman Saputra (Garuda Prestasi Nusantara Consulting, 2026)
This study aims to examine the Effect of Environmental, Social, and Governance (ESG) on the Cost of Debt in Energy Sector Companies Listed on the IDX